Hypoxia‐Related Altitude Illnesses. Issue 4 (11th March 2013) - Netzer, Nikolaus; Strohl, Kingman; Faulhaber, Martin; Gatterer, Hannes; Burtscher, Martin
Abstract : Background: Millions of tourists and climbers visit high altitudes annually. Many unsuspecting and otherwise healthy individuals may get sick when sojourning to these high regions. Acute mountain sickness represents the most common illness, which is usually benign but can rapidly progress to the more severe and potentially fatal forms of high‐altitude cerebral edema and high‐altitude pulmonary edema. Methods: Data were identified by searches of Medline (1965 to May 2012) and references from relevant articles and books. Studies, reviews, and books specifically pertaining to the epidemiology, prevention, and treatment of high‐altitude illnesses in travelers were selected. Results: This review provides information on geographical aspects, physiology/pathophysiology, clinical features, risk factors, and the prevalence of high‐altitude illnesses and also state‐of‐the art recommendations for prevention and treatment of such illnesses. Conclusion: Given an increasing number of recreational activities at high and extreme altitudes, the general practitioner and specialist are in higher demand for medical recommendations regarding the prevention and treatment of altitude illness. Despite an ongoing scientific discussion and controversies about the pathophysiological causes of altitude illness, treatment and prevention recommendations are clearer with increased experience over the last two decades.